Revisiting Paulo Freire as a theoretical base for participatory practices for social workers - Schenck, R (Social Work/Maatskaplike Werk, 2002)
This paper revisits the work of the Brazilian pedagogue, Paolo Freire, and considers the possible impact of his theories for social workers and other helping professionals, particularly in relation to participatory practices. Freire had an enormous influence; some might say his ideas produced a paradigm shift in professionals' perceptions about people, specifically those who were regarded as poor and oppressed. It also became clear that Freire ideas were a watershed in thinking in various fields and disciplines in different countries. Godono (1998:30) refers to a "before and after" Freire and indicates that Freire's work has been read, discussed and applied by thousands of people in a great variety of disciplines. Freire's ideas are particularly important for social workers who attempt to facilitate participatory processes with individuals, couples and families, groups and communities. Freire (1998:141) stated that we cannot train or work impartially as ifwe were wearing gloves and masks in order not to contaminate or not to be contaminated. As Godonoo (1998) points out, many people (including me) have been "contaminated" by Freire's thoughts. Inevitably we have our own ideas and values about and towards people and the world, but reading this article may guide the reader to reflect also on his/her own ideas and values. In this paper I extract and summarise Freire's thinking about and valuing of people which form the basis of, or theory for, his and others' participatory practices . It is hoped that this revisiting of his theory will provide us with guidelines to improve people-centred, participatory practices in social work. In addition to Freire's own writings, many articles have been written and published about Freire. There is also no shortage of comments on or critiques and summaries of the thoughts of Paolo Freire on the Internet. The question can then well be asked what makes this article unique and different from the others. The uniqueness of the article lies mainly in the way Freire's theory is presented. In South Africa we have been deprived of the richness and depth of Freire's thinking for a long time because his work has been banned. We can now explore all he had to offer in working with suffering and disadvantaged people. Freire offers a theory on participatory practices and in particular participatory community development. He enables us to ground our work in wellfounded and formulated ideas. In their manuals Hope and Timmel (1995) give us very practical ideas on how to operationalise Freire's methodology but in this article I have formulated his ideas as a clear, lucid, usable theory. I have concentrated on the optimistic, positive nature of his approach, which really can lead to people's liberation . As there is still oppression and poverty in this country, Freire's approach is as relevant today as it was when he first wrote in 1972.